The false consensus effect disappears if representative information and monetary incentives are given - Dirk Engelmann; Martin Strobel (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
In this paper we present an experiment on the false consensus effect. Unlike previous experiments, we provide monetary incentives for revealing the actual estimation of others' behavior. In each session and round sixteen subjects make a choice between two options simultaneously. Then they estimate the choices of a randomly selected subgroup. For half of the rounds we provide information about other subjects' choices. There we find no false consensus effect. At an aggregate level, subjects significantly underweight rather than overweight their choices. The results are difficult to interpret for the rounds where we do not provide information.
urn:nbn:de:kobv:11-10046555
Keywords: C91; D83; D84; 330